Simulating the Interaction of a Comet With the Solar Wind Using a Magnetohydrodynamic Mode - Evangelista, Edgard de F. D.; Domingues, Margarete O.; Mendes, Odim; Miranda, Oswaldo D. (Discontinuity, Nonlinearity, and Complexity, 2026)
We present simulations of a comet interacting with the solar wind. Such simulations are treated in the framework of the ideal, 2D magnetohydrodynamics (MHD), using the FLASH code in order to solve the equations of such a formalism. Besides, the comet is treated as a spherically symmetric source of ions in the equations of MHD. We generate results considering several scenarios, using different values for the physical parameters of the solar wind and of the comet in each case. Our aim is to study the influence of the solar wind on the characteristics of the comet and, given the nonlinear nature of the MHD, we search for the occurrence of phenomena which are typical of nonlinear systems such as instabilities and turbulence.